The rheological properties of cement pastes containing fly ash with different particle size distribution - Greszczyk, Stefania; Lipowski, Grzegorz (Communications - Scientific letters of the University of Zilina, 2000)
The paper presents the analysis of fly ash influence on rheological properties of cement pastes with content different type of fly ash concerning particle size distribution. It was pointed that rheological properties of cement pastes containing fly ash from bituminous coal (hard coal) depend mostly on content fly ash in cement and on the quantity of fine fraction in fly ash as well as on the shape of fly ash particle.